2016
DOI: 10.3847/1538-4357/833/2/179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Gamow–teller Strengths on Explosive Type Ia Supernova Nucleosynthesis

Abstract: Recent experimental results have confirmed a possible reduction in the Gamow–Teller (GT+) strengths of pf-shell nuclei. These proton-rich nuclei are of relevance in the deflagration and explosive burning phases of SNe Ia. While prior GT strengths result in nucleosynthesis predictions with a lower-than-expected electron fraction, a reduction in the GT+ strength can result in a slightly increased electron fraction compared to previous shell model predictions, though the enhancement is not as large as previous en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 74 publications
10
45
0
Order By: Relevance
“…Studies of nucleosynthesis of one-dimensional models have shown some important dependencies on the model parameters. For example, Fe-peak elements synthesized in the Chandrasekhar mass model W7 (Nomoto et al 1984) is shown to be consistent with the solar abundances, except for a significant overproduction of 58 Ni, where the rate of electron capture is important (e.g., Thielemann et al 1986;Iwamoto et al 1999;Brachwitz et al 2000;Mori et al 2016). The solar abundance pattern of Fe-peak elements can also be reproduced by the sub-Chandra models with solar metallcity (e.g., Shigeyama et al 1992;Nomoto et al 1994), although the Ni/Fe ratio (which depends on metallicity) tends to be under solar because of the low central den-sity of exploding WDs.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies of nucleosynthesis of one-dimensional models have shown some important dependencies on the model parameters. For example, Fe-peak elements synthesized in the Chandrasekhar mass model W7 (Nomoto et al 1984) is shown to be consistent with the solar abundances, except for a significant overproduction of 58 Ni, where the rate of electron capture is important (e.g., Thielemann et al 1986;Iwamoto et al 1999;Brachwitz et al 2000;Mori et al 2016). The solar abundance pattern of Fe-peak elements can also be reproduced by the sub-Chandra models with solar metallcity (e.g., Shigeyama et al 1992;Nomoto et al 1994), although the Ni/Fe ratio (which depends on metallicity) tends to be under solar because of the low central den-sity of exploding WDs.…”
Section: Introductionmentioning
confidence: 93%
“…Due to the availability of new electron capture rates, where the rates for iron-peak elements are in general lower, it is interesting to see if the overproduction problems in the W7 and WDD2 can be alleviated. This is also a study of how the abundance ratios among iron-peak elements depend on electron capture rates and possibly other nuclear reaction rates in view of still existing uncertainties of these rates (see also Mori et al 2016).…”
Section: Effects Of Updated Electron Capture Rates In 1-d Models Wmentioning
confidence: 99%
“…On the other hand, Parikh et al (2013) analysed one threedimensional model of SNIa and the classical one-dimensional W7 model (Thielemann et al 1986), and found maximal sensitivity of SNIa nucleosynthesis to the electron capture rates of the α elements 28 Si, 32 S, and 36 Ar, whereas electron captures on IGN had little impact on the explosion. Recently, Mori et al (2016) have studied the impact that recent alternatives to the shell model calculations of Dean et al (1998), motivated by new experimental data on the electron capture rates on 56 Ni and 55 Co, have on SNIa nucleosynthesis. These data call for differences in the GT + strength distribution, leading to reduced electron capture rates.…”
Section: Introductionmentioning
confidence: 99%
“…These data call for differences in the GT + strength distribution, leading to reduced electron capture rates. Mori et al (2016) found that the overall yields of the explosion are affected at most by 2−3%. Both Mori et al (2016) and Parikh et al (2013) based their sensitivity study on modifying the nuclear rates in nuclear post-processing, meaning that the sensitivity study was decoupled from the supernova hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the over-production factor is suppressed within twice for all neutron-excess Cr, Fe and Ni isotopes [14]. Thus, the over-production problem of neutron-excess iron-group nuclei compared with the solar abundances is coming near to be solved.…”
Section: Nucleosynthesis Of Iron-group Nuclei In Type-ia Supernova Exmentioning
confidence: 98%